Escribo un texto descriptivo de mi mascota favorita - Zoto Paredes, Aida (2021)
The present work of professional sufficiency entitled “I write a descriptive text about my favorite pet ", aims to improve the written production in students, managing to develop the production of short texts (phrases, words); The main objective is for the reader to obtain an exact image of the reality that we are transmitting in words, a kind of “verbal painting”. Therefore, the enumeration of characteristics is the main feature of the descriptive text. The methodology used was based on the curricular plan proposed by the Ministry of Education, it sought to promote the active and meaningful participation of all students. At all times it is intended to awaken the interest and motivation of the student, when writing and producing their short texts, that boys and girls are able to express their needs, feelings and interest in different contexts and situations. Paz (2016) mentions that the description process is divided into three stages. The first is to observe reality, analyzing all the details that we visualize. In the second stage, all the information is arranged in a logical way, so the text can be clearly interpreted. The final stage consists of presenting what was defined in the first two. Therefore, it is convenient for children to learn to observe the objects that surround them and to capture their characteristics; For this, it is essential to carry out oral and written activities in which they have the possibility of occupying all the senses to describe them, it is necessary to make a list of words (adjectives) that help students to describe objects in order to be able to construct sentences.